Intrathecal sufentanil or fentanyl as adjuvants to low dose bupivacaine in endoscopic urological procedures - Shikha Gupta; Supriya Sampley; Suneet Kathuria; Sunil Katyal (Journal of Anaesthesiology Clinical Pharmacology, 2013)
Context: Opioids are being increasingly used these days as adjuvants to local anesthetics in spinal anesthesia. Aim: The aim of this study is to compare the effects of adding sufentanil or fentanyl to low dose bupivacaine in spinal anesthesia for endoscopic urological procedures. Settings and Design: Prospective, randomized, double-blind study. Materials and Methods: A total of 90 elective endoscopic urological surgery patients, 40-80 years old, received spinal anesthesia with 7.5 mg hyperbaric bupivacaine 0.5% (Group A) or by adding sufentanil 10 g (Group B) or fentanyl 25 g (Group C) to 5 mg hyperbaric bupivacaine 0.5%. These groups were compared in terms of the quality of spinal anesthesia as well as analgesia. Statistical analysis used: Analysis of variance and Chi-square test. Results: The onset of sensory and motor blockade was significantly rapid in Group A as compared with Groups B and C. The maximum upper level of sensory block was higher in Group A patients than Groups B and C patients. Quality of analgesia was significantly better and prolonged in sufentanil group as compared with other two groups. Motor block was more intense and prolonged in Group A as compared with Groups B and C patients. Request for post-operative analgesic was significantly delayed in Group B patients. Conclusions: Spinal anesthesia for endoscopic urological procedures in elderly patients using low dose bupivacaine (5 mg) combined with 10 μg sufentanil is associated with a lower incidence of hemodynamic instability, better quality and prolonged duration as compared to that by adding 25 μg fentanyl.